2006
DOI: 10.1152/ajpendo.00200.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue compensates for defect of phosphatidylinositol 3′-kinase induced in liver and muscle by dietary fish oil in fed rats

Abstract: The present work aimed to study in rats whether substitution of a low level of fish oil (FO; 2.2% of calories) into a low-fat diet (6.6% of calories from fat as peanut-rape oil or control diet) 1) has a tissue-specific effect on insulin signaling pathway and 2) prevents dexamethasone-induced alteration of insulin signaling in liver, muscle, and adipose tissue. Sixteen rats were used for study of insulin signaling, and sixteen rats received an oral glucose load (3 g/kg). Eight rats/group consumed control diet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 44 publications
4
34
1
Order By: Relevance
“…This effect may have been mediated by increased insulin sensitization and/or decreased glucagon and epinephrine action in response to the reduction in cortisol during 11␤-HSD1 inhibition. Cortisol can decrease insulin receptor binding (13) and affect postreceptor insulin action (50) in part by decreasing PI3K activity (11). Cortisol has also been shown to maintain physiological glycogen phosphorylase levels (52) and increase glucagon binding to hepatocytes (15).…”
Section: Discussionmentioning
confidence: 99%
“…This effect may have been mediated by increased insulin sensitization and/or decreased glucagon and epinephrine action in response to the reduction in cortisol during 11␤-HSD1 inhibition. Cortisol can decrease insulin receptor binding (13) and affect postreceptor insulin action (50) in part by decreasing PI3K activity (11). Cortisol has also been shown to maintain physiological glycogen phosphorylase levels (52) and increase glucagon binding to hepatocytes (15).…”
Section: Discussionmentioning
confidence: 99%
“…GC treatment leads to a down-regulation of IRS1 and IRS2 proteins, blunting intracellular insulin signal transduction [176]. Additionally, phosphoinositide 3 (PI3) kinase activity as well as Akt phosphorylation as markers of insulin signaling strength represent negative targets of GC action in rat adipocytes [177,178]. The inhibitory effect on post-receptor insulin signaling is then also translated into impaired glucose uptake by the glucose transporter 4 (Glut4).…”
Section: Lipolytic Functions Of Gcsmentioning
confidence: 99%
“…In rats fed a high-fat diet rich in linoleic acid, insulin-induced PI 3-kinase activity is markedly depressed in liver and skeletal muscle, as well as its expression in adipose tissue (39). Moreover, in rats treated with a synthetic glucocorticoid (dexamethasone) that induces insulin resistance, PI 3-kinase activity stimulated by either insulin (32) or fed state (12) is deeply depressed in liver, muscle, and adipose tissue. Downstream to PI 3-kinase, activation of serine-threonine kinase Akt, a protein that plays a pivotal role in regulation of glucose transporter 4 (GLUT4) trafficking (42), is impaired in both muscle and adipose tissue of patients with type 2 diabetes (43).…”
mentioning
confidence: 99%
“…Substitution of one-third of sunflower oil (rich in linoleic acid) by fish oil into a high-fat diet (60% of energy as fat) in rats completely prevents the decrease of PI 3-kinase activity and expression in muscle and adipose tissue, respectively (39). Recently, we demonstrated that substitution of a low amount of fish oil, 4.9% of metabolizable energy (ME), into a normolipidic diet containing 14.6% of energy as peanut-rape oil induced, in fed rats, a decrease in PI 3-kinase activity in both liver and muscle while activating it in adipose tissue (12). The increase in PI 3-kinase activity in adipose tissue could have compensated for its decrease in liver and muscle, which could explain how glucose tolerance and insulin sensitivity remained unaffected (12).…”
mentioning
confidence: 99%